Analysis and Design of Queue Service Information System Integrated with WhatsApp using UML Method - Purnama, Ega Bagus; Azizah, Nurul; Nuraminudin, M; Dewi, Melany Mustika (Institut Teknologi Bisnis AAS Indonesia, 2024)
In the rapidly developing digital era, information systems have become an important element in increasing efficiency and effectiveness in various activities. As an important part of public services, queuing services withstand significant challenges in managing rapid population growth. Long waiting times and inefficient queue management can result in user dissatisfaction, increased workload for service providers, and potentially harm productivity. This research aims to overcome these challenges by identifying, pivoting, and creating an innovative information system integrated with the popular cross-platform application, WhatsApp. The main focus is automating queue service management to increase efficiency and user convenience. The resulting system is expected to provide significant changes in public services, reduce waiting times, and make queue management easier. The Unified Modeling Language (UML) methodology is used in the design of this system, providing systematic guidance to achieve these goals. In this research, we identify problems, user needs, functional requirements, and non-functional systems, including queue registration, queue management, user management, and service management. The results include use case diagrams, activity diagrams, sequence diagrams, and class diagrams, which provide a detailed overview of various aspects of the system. The results of this research can serve as a guide for application developers and demonstrate the benefits of UML in designing complex information systems.